2021
DOI: 10.46827/ejsss.v6i2.1012
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Distance Learning Processes and University Students’ Anxiety in Times of Covid19

Abstract: Governments worldwide have implemented strict physical and social distancing measures to prevent contamination from the COVID-19 pandemic and flatten the epidemic curve. Recent findings show that university students have experienced increased anxiety and moderate-to-severe stress because of confinement measures (quarantine) (Husky et al., 2020; Islam et al., 2020). In Cyprus, universities switched to distance learning in mid-March 2020. The present research examined the social and academic challenges that univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Also, Hadjicharalambous et al (2021) confirmed that people who enjoyed good cooperation between their family members regarding daily activities exhibited higher scores on general health and quality of life, positive mood, and physical and psychological health. Furthermore, Demetriou et al (2021) revealed that students who resided with their families during the lockdown had significantly lower stress levels than those who did not; in fact, the students who were surrounded by family reported less frequent terror symptoms than the students who were living alone during that time.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Also, Hadjicharalambous et al (2021) confirmed that people who enjoyed good cooperation between their family members regarding daily activities exhibited higher scores on general health and quality of life, positive mood, and physical and psychological health. Furthermore, Demetriou et al (2021) revealed that students who resided with their families during the lockdown had significantly lower stress levels than those who did not; in fact, the students who were surrounded by family reported less frequent terror symptoms than the students who were living alone during that time.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies conducted worldwide, show clearly that the Covid19 pandemic has severely affected young adults' mental health and subsequent quality of life (Cao et al, Demetriou et al, 2021). The restrictions in movement and in gathering capacities have negatively impacted productivity and performance and, especially in young adults, have suspended personal freedoms, independence and perhaps adulthood itself.…”
Section: Effects Of Covid19 Restrictive Measures On University Student Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…He argued that a difference between a learner’s anticipation, experience, and apprehension from technology among learners can justify the reason for learners’ FLA and online learning anxiety. Demetriou et al (2021) explored the relationships between employed and unemployed learners’ FLA levels and their adaptableness to online learning during the lockdown. They found that employment is significantly correlated with online learning and anxiety levels.…”
Section: Literature Reviewmentioning
confidence: 99%